Główne zmiany czekające profesję biegłego rewidenta w Polsce w świetle uwarunkowań Dyrektywy 2006/43/WE - Chorostkowski, Maciej (Main changes addressed to profession of statutory auditors in Poland in the light of requirements of Directive 2006/43/EC, 2008)
There were several spectacular collapses of big companies due to misleading financial reporting last years. It resulted in adopting new regulations either to bring back the public confidence in financial reporting or raise the quality of audit of financial statements. In the United States of America the reply to these scandals was a Sarbanes-Oxley Act, whereas in the European Union - Directive 2006/43/EC. The Directive will change the working of statutory auditors also in Poland. The most important changes will encompass: creating the public oversight system over the profession of statutory auditors, establishing a new definition of the independence of a statutory auditor, implementing international standards on auditing, determining new requirements on the structure of the members of the administrative or management body and defining new grounds of the quality assurance system and public register of auditors. The paper attempts to identify the changes in the profession of statutory auditors due to regulations of the Directive in Poland.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 48-55